MEMBEDAH BLUE OCEAN STRATEGY: BAGAIMANA PESANTREN KECIL BISA BERSAING DENGAN SEKOLAH INTERNASIONAL - Fatimatul Munawaroh; Muhammad Imam Khaudli (As-Sulthan Journal of Education, 2026)
This article explores a new paradigm in the management and development of Islamic education through the concept of "Pesantren 5.0." Amidst the wave of technological disruption, Islamic boarding schools (pesantren) face significant challenges in maintaining the authenticity of the "Kitab Kuning" (classical text) literacy tradition while adapting to the efficiencies offered by Artificial Intelligence (AI). This study aims to formulate an integration model where AI technology is not perceived as a threat to the religious authority of the Kyai, but rather as an acceleration instrument in learning methodologies and institutional management. Using a qualitative-descriptive approach, this article dissects how the implementation of AI-based tools can assist students (santri) in performing rapid cross-reference searches within classical texts, conducting deeper textual analysis, and automating pesantren administration for greater transparency. The discussion reveals that the key to the future development of pesantren lies in "hybrid pedagogy" maintaining spirituality and the chain of knowledge (sanad) through personal, human interaction, while cognitive and operational processes are supported by intelligent digital systems. Consequently, Pesantren 5.0 is not merely about the digitalization of physical facilities but involves a transformation of the educational management mindset to create a learning ecosystem relevant to industrial needs without uprooting core boarding school values.